The role of industry conditions in shaping job security and employee commitment - Odoom, Samuel Kwesi (Technium Social Sciences Journal, 2025)
The study examined how examined how industrial conditions shape job security and employee commitment. Using the social exchange theory, the study contended that industrial conditions would have negative implications on job security and employee commitment. Through a quantitative analysis and cross-sectional survey, 345 persons were sampled for the study. The results were at variance with the contention of the study. The results revealed that industrial conditions rather has significant relationship with job security and also has positive effect on employee commitment